Inovasi strategi media da’wah dalam upaya peningkatan pemahaman keagamaan pada masa pendemic covid 19 di Kecamatan Cileungsi - Tahir (At Turots: Jurnal Pendidikan Islam, 2023)
Understanding of religious teachings can be assessed as a stimulus that has an impact on one's religious behavior. Understanding of religion as an activity based on believed religious values is influenced by the intensity of individual activity in using da'wah media, in the use of da'wah media as a means to increase religion it turns out to be more influenced by YouTube. The purpose of this study is to find out the da'wah media in increasing religion. As well as strategic innovation efforts to improve da'wah media in an effort to increase religious understanding. By knowing this goal, it is hoped that there will be improvements for preachers and da'wah institutions so that maximum results can be obtained in preaching. This study uses quantitative methods, descriptive analysis, data collection techniques by questionnaire, interview methods, and documentation methods. While the population in this study amounted to 45 respondents with a sample of 37 respondents. Analyzing the author's data using the Chi Square formula. The results obtained were (x2 hits) 30.59 greater than the chi squared table (x2 tabs) both at a significant level of 5%, namely 5.991 and at a significant level of 1%, namely 9.210 and it can also be seen from the results of data analysis of KK of 0.7 in the category enough. Therefore, the hypothesis used is that "Innovation in da'wah media strategies is very influential and is very much needed in efforts to increase religious understanding in Cileungsi.